Challenge with lipopolysaccharides or Freund's adjuvant? What is the best option to trigger acute phase protein production in broilers?. (April 2015) - Koppenol, A.; Everaert, N.; Buyse, J.; Delezie, E.
Highlights: LPS is a better agent to trigger acute phase protein production in broilers, compared to FA. OVT and AGP have a more pronounced production after challenge, compared to CP, making them better biomarkers. Best time point for APP determination is 24 h PI. Abstract: Broilers were injected at 10 days of age with either Escherichia coli lipopolysaccharides (LPS) or with Freund's adjuvants (FA) to investigate its triggering effect on the acute phase reaction (APR). First the kinetics of certain APP was studied by sampling blood 4 h, 8 h, 12 h and 24 h post injection with LPS. Ovotransferrin (OVT) and α-1 acid glycoprotein (AGP) concentration increased with time post injection (PI) with LPS to reach a plateau at 12 and 24 h PI. Caeruloplasmin (CP) did not increase with time PI. Compared to injection with phosphate buffered saline, OVT concentrations were higher when injecting chicks with LPS at all time points PI. At 24 h PI, LPS injection resulted in higher OVT and AGP concentration compared to injection with FA. It is recommended to use LPS instead of FA to trigger the APR. The best time point to sample blood for APP determination is 24 h PI.